Reforming the investment climate : lessons for practitioners - Kikeri, Sunita; Kenyon, Thomas (Thomas John); Palmade, Vincent; International Finance Corporation; World Bank. (Washington, D.C. : International Finance Corporation : World Bank, 2006)
Most people agree that a good investment climate is essential for growth and poverty reduction. Less clear is how to achieve it. Many reforms are complex, involving more than technical design and content. They are both political, facing opposition from organized and powerful groups-and institutionally demanding, cutting across different departments and levels of government. Reform thus requires paying as much attention to understanding the politics and institutional dimensions as to policy substance, which is the goal of this paper. Drawing from more than 25 case studies, it shows that there is no single recipe or "manual" for reform, given diverse contexts and serendipity in any reform effort. But three broad lessons emerge. The first is to recognize and seize opportunities for reform. Crisis and new governments are important catalysts, but so is the competition generated by trade integration and new benchmarking information. The second is to invest early in the politics of reform. Central to this process is using education and persuasion strategies to gain wider acceptance and neutralize opponents. Pilot programs can be valuable for demonstrating the benefits and feasibility of change. And the third is to pay greater attention to implementation and monitoring. This does not require full scale public management reforms. Reformers can draw on private sector change management techniques to revitalize public institutions responsible for implementation. Given the cross-cutting nature of reform, new oversight mechanisms may be needed to monitor and sustain reform. The paper concludes with an emerging checklist for reformers and identifies areas for future work.
Includes bibliographical references (p. 105-109).
Also available on the World Wide Web.
Keywords: Investments -- Case studies; Economic policy -- Case studies; Social policy -- Case studies